Maulid Nabi sebagai Ekspresi Kebudayaan; Kajian Sosiolinguistik tentang Konsep Identitas Masyarakat - Mochamad Syaifudin (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2022)
This article comes from a special feature on the birthday celebrations of the Prophet Muhammad Thor, who is impressive in many places. By the way, they differ in terms of exercises, but they also differ in the use of melodic terms and readings in all celebrations. Besides, the distinctions in wording and texts that are perused time make a sort of friendly character. Assuming you have a place with specific gathering the terms and text you read will be unique in the event that somebody moves to another gathering. This essay is an archive of several references that describe subjective research techniques using information classification strategies such as member perceptions and indoor and outdoor interviews, as well as the habit of recognizing the birthday of the Prophet Muhammad. is included. In information research, research in social linguistics is presented in a refractory manner. You can infer very well from this paper. First, the memory of the birthday of the Prophet Muhammad Thor, the legitimacy of his execution as a superculture. The way of life, depending on the region, class, identity, and calling, completes the structure and technique to remember the birthday of the Prophet Muhammad. When maulid is done dependent on nearby insight (locale, class, identity, and calling) then, at that point, extraordinary variety shows up in certains regions and doesn't struggle with the parent cultture. This is alluded to as a subculture. Assuming it struggle with the parent culture the peculiarity is known as a nonconformity. Second, the recognition of the birthday of the Prophet Muhammad Considered a muslim strict peculiarity, particularly Indonesian Muslim, has gone through changes in the terms of simplication because of language impediment, just being gone against between the sunnah or bid'ah segment, just as encountering social personality where the utilization of names, and readings that are perused show about specific strict associations.